'Playing the game': How do surgical trainees seek feedback using workplace‐based assessment?. Issue 9 (18th August 2017) - Gaunt, Anne; Patel, Abhilasha; Rusius, Victoria; Royle, T James; Markham, Deborah H; Pawlikowska, Teresa
Abstract : Objectives: Although trainees and trainers find feedback interactions beneficial, difficulties in giving and receiving feedback are reported. Few studies have explored what drives trainees to seek feedback. This study explores how workplace‐based assessments (WBAs) influence the ways surgical trainees seek feedback and feedback interactions. Methods: Utilising a template analysis approach, we conducted 10 focus groups with 42 surgical trainees from four regions across the UK. Data were independently coded by three researchers, incorporating three a priori themes identified from a previous quantitative study. Further themes emerged from exploration of these data. The final template, agreed by the three researchers, was applied to all focus group transcripts. The themes were linked in a diagrammatical form to allow critical exploration of the data. Results: Trainees' perceptions of the purpose of WBA for learning or an assessment of learning, and their relationship with their trainer impacted upon how trainees chose to use WBA. Perceiving WBA as a test led trainees to 'play the game': seek positive and avoid negative feedback through WBA. Perceiving WBA as a chance to learn led trainees to seek negative feedback. Some trainees sought negative feedback outside WBA. Negative feedback was more important for changing practice compared with positive feedback, which enabled trainees to 'look good' but had less of an effect on changing clinical practice. The timing of feedback relative to WBA was also important, with immediate feedback being more beneficial for learning; however, delayed feedback was still sought using WBA. Discussion: Trainees' perceptions of the purpose of WBA and their relationship with their trainer informed when they chose to seek feedback. Trainees who perceived WBA as a test were led to 'play the game' by seeking positive and avoiding negative feedback. Outside of WBA, trainees sought negative feedback, which was most important for change in practice.